Vaginal Dysbiotic Microbiome in Women With No Symptoms of Genital Infections - Pramanick, Rinku; Nathani, Neelam; Warke, Himangi; Mayadeo, Niranjan; Aranha, Clara (Frontiers in Cellular and Infection Microbiology, 2022)
The vaginal microbiome plays a critical role in determining the progression of female genital tract infections; however, little is known about the vaginal microbiota of Indian women. We aimed to investigate the vaginal microbial architecture of women with asymptomatic bacterial vaginosis (BV) (n=20) and normal microbiota (n=19). Microbial diversity was analyzed in vaginal swabs from regularly menstruating women (18-45yrs) by 16S rRNA V3-V4 amplicon (MiSeq Illumina) sequencing. Alpha diversity as measured by Pielou's evenness revealed microbial diversity was significantly greater in BV samples than normal microbiota(p= 0.0165). Beta diversity using UniFrac metrics indicated distinct microbial communities clustering between normal and BV flora. Firmicutes were the major phyla in vaginal specimens of normal microbiota whereas Actinobacteria, Fusobacteria, Bacteroidetes were significantly abundant in BV samples. Notably, relative abundance of Lactobacillus was significantly high in normal microbiota. Conversely Gardnerella, Sneathia, Prevotella, Atopobium, Ureaplasma, Dialister significantly dominated dysbiotic microbiota. Relative frequency of Lactobacillus decreased significantly in BV (6%) compared to normal microbiota (35.2%). L. fermentum, L. gasseri, L. iners, L. jensenii, L. mucosae, L. ruminis, L. salivarius, L. coleohominis were exclusively present in normal microbiota. L. iners was detected from both the groups with relative frequency of 50.4% and 17.2% in normal and BV microbiota respectively. Lefse analysis indicated Atopobium vaginae, Sneathia amnii, Mycoplasma hominis Prevotella disiens as biomarkers for dysbiosis and L. jensenii as a biomarker of a healthy microbiota. Firmicutes were negatively correlated to Tenericutes, Actinobacteria, Bacteroidetes, and Fusobacteria. Proteobacteria positively correlated to Tenericutes, and Bacteroidetes were shown to be positively correlated to Fusobacteria. Predicted functional analysis indicated differences in the functional profiles between BV and normal microbiota. Normal microbiota utilized pathways essential for phosphatidylglycerol biosynthesis I & II, peptidoglycan biosynthesis, geranylgeranyl diphosphate biosynthesis I, mevalonate pathway, CoA biosynthesis pathway I and pyrimidine nucleotide salvage; whereas BV bacteria had characteristic aromatic amino acid biosynthesis, pentose phosphate pathway, carbohydrate degradation. In conclusion, women with asymptomatic BV have vaginal microbiota significantly different than women with normal microbiota. Furthermore, the study provides insights into the vaginal microbial structure of Indian women that will enable us to explore the prospective candidates for restoring the vaginal microbiota.